A Multilevel Analysis of Regressors of Access to Improved Drinking Water and Sanitation Facilities in Ghana. (4th June 2019) - Agbadi, Pascal; Darkwah, Ernest; Kenney, Paul L.
Abstract : People's access to quality water and sanitation resources significantly improves their health. Using the 2014 Ghana DHS dataset, multilevel robust Poisson regression modelling was performed to investigate the factors that enhance Ghanaian households' access to improved sources of drinking water and toilet facilities. The results indicated that household head and household socioeconomic factors have significant effects on access to improved sources of drinking water and toilet facilities, and this varies from one community of residence to another. The following households had a higher probability of having access to improved sources of drinking water: female-headed households, households with heads who had at least attained middle-school-level education, urban households, and nonpoorest households. Correspondingly, the following households were more likely to have access to improved toilet facilities: female-headed households had a higher chance of access, as well as those whose heads had at least middle-school-level education, were at least 35 years old, or were currently married, rural households, households with a minimum of seven members, and households who attained at least middle wealth status. In their efforts to increase citizens' access to improved water and sanitation facilities, the government and other development organizations should develop citizens' wealth-creation capacities and enable their attainment of formal education.